Complete mitochondrial genome of the South Polar Skua Stercorarius maccormicki (Charadriiformes, Stercorariidae) in Antarctica. (3rd May 2016) - Han, Yeong-Deok; Baek, Ye-Seul; Kim, Jeong-Hoon; Choi, Han-Gu; Kim, Sanghee
Abstract: The South Polar Skua, gull-like seabirds is the most fascinating Antarctic seabirds that lay two eggs at sites free of snow and ice and predominantly hunt pelagic fish and penguins. Blood samples of the South Polar Skua Stercorarius maccormicki was collected during the summer activity near King Sejong station in Antarctica. The complete mitochondrial DNA sequence of S. maccormicki was 16, 669 bp, showing conserved genome structure and orientation found in other avian species. The control region of S. maccormicki was 93- and 80 bp shorter compared to those of Chroicocephalus saundersi and Synthliboramphus antiquus r espectively. Interestingly, there is a (CAACAAACAA)6 repeat sequence in the control region. Our results of S. maccormicki mt genome including the repeat sequence, may provide useful genetic information for phylogenetic and phylogeographic histories of the southern skua complex.